Efektivitas Kedisiplinan Guru Terhadap Hasil Belajar Bahasa Arab Siswa Madrasah Tsanawiyah Miftahul Huda Kalirejo Sukorejo Pasuruan - Zaenabul Mukarromah (CV. Satria Jaya, 2023)
Teacher discipline is compliance with institutional regulations without violations. Learning outcomes are the achievements of students who previously experienced the learning stages. The objectives of the study: To determine Teacher Discipline at Madrasah Tsanawiyah Miftahul Huda, To determine Arabic learning outcomes of Madrasah Tsanawiyah Miftahul Huda students, To determine the effect of Teacher Discipline on Arabic learning outcomes of Madrasah Tsanawiyah Miftahul Huda students, the approach used was quantitative with facto exposure type. . data analysis using questionnaires and documentation. The results of the study found that the teacher's discipline was in the low category because 0.340 is less than 0.532, while student learning outcomes were in the very low category because 0.027 is less than 0.532 with the Shapiro-Wilk technique. the influence of teacher discipline on students' Arabic learning outcomes has a low significance with the person correlation technique with a significance value of 0.175 is greather than 0.05, meaning that the two variables are not correlated with a standard correlation value of 0.384, which means that the correlation of the two variables is categorized as low. the influence of teacher discipline on students' Arabic learning outcomes has a significance level of 14.7% and the rest is influenced by other variables not included in the researching.